PENGARUH EDUKASI TENTANG STUNTING TERHADAP PEMGETAHUAN DAN SIKAP IBU YANG MEMPUNYAI ANAK STUNTING - Munir, Zainal; Audyna, Lina (Jurnal Keperawatan Profesional, 2022)
Background: Stunting is a chronic malnutrition problem caused by lack of nutritional intake in children for a long time, so that it can lead to growth disorders in children Objective: to determine the effect of education about stunting on the knowledge and attitudes of mothers who have stunting children . Methods: The sources of the articles used were obtained from searches through the databases of Google Scholar, Pubmed, Google Cindekia and Cambridge. Article search is restricted from 2017-2022. After the article is obtained, then the article is reviewed until the stage of making a literature review. The keywords used in the search for articles are the effect of stunting education on mother's knowledge of caring for stunting children and the effect of stunting education on mothers caring for stunting children. This literature review uses 15 articles that meet the inclusion criteria. Results: there is an effect of providing education to mothers who have stunting children. Conclusion: educational interventions for mothers with stunting children can affect the quality of attitudes and behavior of mothers in the care of stunting children.